Determination of moisture gradient and mass attenuation Coefficient of wood samples using gamma radiation - Kumar, Rajeev; Kaur, Charanjeet (Indian Journal of Agroforestry, 2025)
The present study is used to measure the mass attenuation coefficient and moisture gradient in sal and jamun species of wood. The moisture gradient of sal and jamun was determined with the use of gamma ray transmission method which involves NaI(Tl) scintillator detector and 137Cs  of  662 keV as gamma source. The mass attenuation coefficients were estimated as the slope of the fitted plot of measured logarithmic relative transmission versus thickness of wood absorber at various moisture levels. The obtained mass attenuation coefficients were used to determine the density of wood samples. The obtained mass attenuations coefficient at different moisture levels were plotted against the relative moisture content and was observed that attenuation coefficient increases with decreasing moisture content, i.e., mass attenuation coefficient is least for completely wet sample and is highest for the oven dried sample. The moisture gradient was observed to follow decreasing exponential trend along the radial direction of the wood in which moisture was induced. The density measured using radiation method agrees well with that from conventional method.